2021
DOI: 10.3390/ijms222212158
|View full text |Cite
|
Sign up to set email alerts
|

Tau Cleavage Contributes to Cognitive Dysfunction in Strepto-Zotocin-Induced Sporadic Alzheimer’s Disease (sAD) Mouse Model

Abstract: Tau cleavage plays a crucial role in the onset and progression of Alzheimer’s Disease (AD), a widespread neurodegenerative disease whose incidence is expected to increase in the next years. While genetic and familial forms of AD (fAD) occurring early in life represent less than 1%, the sporadic and late-onset ones (sAD) are the most common, with ageing being an important risk factor. Intracerebroventricular (ICV) infusion of streptozotocin (STZ)—a compound used in the systemic induction of diabetes due to its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 132 publications
(249 reference statements)
2
19
0
Order By: Relevance
“…Of interest, the immunoreactivity for these AD markers increased in a time-dependent fashion, starting from p21, implying the development in adulthood. The presence of APP/Aβ1-42 deposits and overexpressed tau in the peripheral retina was previously reported in transgenic AD mice ( Ning et al, 2008 ; Dutescu et al, 2009 ; Kocherhans et al, 2010 ; Latina et al, 2021a ), and particularly this pathological expression was confirmed in post-mortem AD retinas ( den Haan et al, 2018 ). Gliosis, Drusen and APP/Aβ deposition represent common markers of neurodegeneration in AMD and AD retinas, resulting from damaged RGCs, activated Macroglia (Muller Cells and astrocytes) and reactive Microglia ( Lee and Landreth, 2010 ).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Of interest, the immunoreactivity for these AD markers increased in a time-dependent fashion, starting from p21, implying the development in adulthood. The presence of APP/Aβ1-42 deposits and overexpressed tau in the peripheral retina was previously reported in transgenic AD mice ( Ning et al, 2008 ; Dutescu et al, 2009 ; Kocherhans et al, 2010 ; Latina et al, 2021a ), and particularly this pathological expression was confirmed in post-mortem AD retinas ( den Haan et al, 2018 ). Gliosis, Drusen and APP/Aβ deposition represent common markers of neurodegeneration in AMD and AD retinas, resulting from damaged RGCs, activated Macroglia (Muller Cells and astrocytes) and reactive Microglia ( Lee and Landreth, 2010 ).…”
Section: Discussionsupporting
confidence: 66%
“…Paraffine-embedded retinas (9 Reeler and 9 WT; 1 retina = 5 slides = 3 optic fields per slide) were sectioned and subjected to double-immunofluorescence. Briefly, dewaxed and post-fixed (2% buffered ρ-Formaldehyde; PFA) sections were equilibrated in PBS [10 mM phosphate buffer and 137 mM NaCl; pH 7.5], quenched (10 mM NH 4 Cl), permeabilized (0.5% Triton X100 in PBS; PBS-TX) and probed with the following antibodies: anti-mouse APP (B4) (sc-28365; 1/100; Santa Cruz Biotechnology; Dallas, Texas, USA); anti-rabbit Aβ1-42 peptide (D54D2) (mAb #8243; 1:100; Cell Signalling Technology, Inc.; Danvers, Massachusetts, USA); anti-rabbit caspase-cleaved protein (CCP)-NH 2 tau 4268; 1/200 Amadoro et al, 2012 ; Latina et al, 2021a , b ) and anti-rabbit TLR4 (H-80) antibody (sc-10741; 1/100; Santa Cruz) as shown in Table 1A . The specific binding was detected using Cy2/Cy3-conjugated specie-specific secondary antibodies (1/500-1/700; Jackson ImmunoResearch Labs., Europe Ltd., Suffolk, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the pathophysiology of the ICV-STZ animal model is similar to that of AD patients [ 47 ]. Furthermore, ICV-STZ has now been found to induce cognitive impairment and neuron damage [ 48 ], oxidative stress [ 49 ] and glucose/energy metabolism damage in the brain [ 50 ], insulin resistance in the brain [ 51 , 52 ], and finally lead to Tau hyperphosphorylation and Aβ deposition [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, based on in vitro and in vivo evidence supporting the crucial role of Tau modifications in driving AD progression [40], administration of another mAb, called 12A12, turn out to be greatly effective in different preclinical AD animal models leading to 'significant improvements' of the main alterations associated with the disease. 12A12 has a very high specificity for a toxic AD-relevant Tau fragment that is capable of causing alterations mainly at the mitochondrial level [41]. This antibody has been developed by the research group coordinated by Pietro Calissano, longtime collaborator of the Nobel laureate Rita Levi-Montalcini, at the Ebri Foundation.…”
Section: Introductionmentioning
confidence: 99%